2018
DOI: 10.1016/j.wneu.2018.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology and Nonsurgical Treatment of Chronic Subdural Hematoma: From Past to Present to Future

Abstract: Based on pathophysiologic mechanisms, animal experiments, and small patient studies, medical treatment may play a role in the treatment of CSDH. There is a lack of level I evidence in the nonsurgical treatment of CSDH. Therefore, randomized controlled trials, currently lacking, are needed to assess which treatment is most effective in each individual patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
128
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(139 citation statements)
references
References 89 publications
2
128
1
8
Order By: Relevance
“…In the present study, patients presenting with recurrence of CSDH after previous surgery were excluded. We also excluded asymptomatic patients since the current literature does not provide sufficient data to justify an additional intervention in this population, especially as some asymptomatic CSDHs spontaneously resorb or resorb with conservative treatments 25. Some trials of MMA embolization as an alternative to surgery for symptomatic patients have been reported,14 15 26 but a detailed description of their symptomatic status is necessary to carefully assess the efficacy of MMA embolization in this specific cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, patients presenting with recurrence of CSDH after previous surgery were excluded. We also excluded asymptomatic patients since the current literature does not provide sufficient data to justify an additional intervention in this population, especially as some asymptomatic CSDHs spontaneously resorb or resorb with conservative treatments 25. Some trials of MMA embolization as an alternative to surgery for symptomatic patients have been reported,14 15 26 but a detailed description of their symptomatic status is necessary to carefully assess the efficacy of MMA embolization in this specific cohort.…”
Section: Discussionmentioning
confidence: 99%
“…17,20) This is one of the most convincing hypotheses regarding the pathogenesis of CSDH. 21,22) Furthermore, the inner membrane consists of collagen and fibroblasts only and is considered nonfunctional in the development of CSDH. 20) On the other hand, the outer membrane, which contains layers of fibroblasts and collagen fibers with inflammatory cells such as neutrophils, lymphocytes, macrophages, and eosinophils 17) is considered important for driving CSDH growth.…”
Section: Pathophysiology Of Csdhmentioning
confidence: 99%
“…In patients with CSDH, high VEGF concentration in the hematoma fluid is of major pathophysiological importance in the generation and steady increase of the hematoma volume, which is essential for the formation and remodeling of new vessels [4]. VEGF and the proangiogenic factor angiopoietin 2 create an unstable Evidence-Based Complementary and Alternative Medicine condition with the continuous formation of new and immature capillaries causing extravasation and recurrent microbleeds [16]. Ang-1 can stabilize newly formed blood vessels after pathological insults in mice and stabilize the cortical actin cytoskeleton and promote cell junction integrity and decrease expression of Ang-2 and inflammatory genes in cultured endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, several nonsurgical treatments, such as dexamethasone, cholesterol-lowering drug, and angiotensin-converting enzyme inhibitors which target the inflammation and angiogenesis, are used to treat CSDH [16]. Cholesterol-lowering drug atorvastatin can decrease the TNF-α and IL-6 level as well as VEGF gene expression in rat model [25], and clinical trial also showed atorvastatin may be a safe and efficacious nonsurgical alternative for treating patients with CSDH [26].…”
Section: Discussionmentioning
confidence: 99%